Chiral Quantum Optics and Optical Nonreciprocity Based on Susceptibility‐Momentum Locking. Issue 8 (19th June 2022) - Tang, Lei; Tang, Jiang‐shan; Xia, Keyu
Abstract: The progress in chiral light–matter interaction in the quantum regime leads to emergence of chiral quantum optics and quantum nonreciprocity. Spin‐momentum locking is at the heart of chiral quantum optics. In this short review, the basic knowledge of optical nonreciprocity and susceptibility‐momentum locking (SML) is introduced as a novel mechanism for conducting chiral quantum optics. Various approaches achieving optical nonreciprocity based on SML are also reviewed. A perspective regarding the challenges in this direction will also be provided. Abstract : Chiral quantum optics based on spin‐momentum locking is a breakthrough in quantum science and technology. This review introduces the newly revealed susceptibility‐momentum locking as a mechanism for conducting chiral quantum optics. It includes the explanation of susceptibility‐momentum locking, the remarkable progresses in that direction, the comparison of the two mechanisms and a stimulating perspective.